Tensile properties and morphological studies on HA/PLA biocomposites for tissue engineering scaffolds - Nainar, S. Mohammed; Begum, Shahida; Ansari, M.N.M.; Anuar, Hazleen (IJER, 2014)
This paper investigates the tensile properties and the morphology of the fractured surface of the biomimetic composite scaffold material which is used to fabricate the scaffold that grows the hard tissue like substances. Morphology of the fractured surface was analyzed under scanning electron microscopy (SEM).